2020
DOI: 10.3847/1538-4357/aba49c
|View full text |Cite
|
Sign up to set email alerts
|

Project AMIGA: The Circumgalactic Medium of Andromeda*

Abstract: Project AMIGA (Absorption Maps In the Gas of Andromeda) is a survey of the circumgalactic medium (CGM) of Andromeda (M31, R vir ;300 kpc) along 43 QSO sightlines at impact parameters 25 R569 kpc (25 at RR vir). We use ultraviolet absorption measurements of Si II, Si III, Si IV, C II, and C IV from the Hubble Space Telescope/Cosmic Origins Spectrograph and O VI from the Far Ultraviolet Spectroscopic Explorer to provide an unparalleled look at how the physical conditions and metals are distributed in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 186 publications
5
85
2
Order By: Relevance
“…C16 derived azimuthally averaged RGB metallicities spanning 70 projected kpc along the GSS by modeling PAndAS CMDs as a combination of weighted isochrones and an MW foreground contamination model (Martin et al 2013). C18 obtained CMD-based metallicities for individual RGB candidates in pencil-beam Hubble Space Telescope/Advanced Camera for Surveys fields from Project AMIGA (Lehner et al 2020) and Brown et al (2006) targeting the GSS at 21, 52, and 80 projected kpc. Neither C16 nor C18 correct for contamination of the GSS by M31ʼs kinematically hot stellar halo, although they show that 1) fields probing the GSS in M31-centric coordinates.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…C16 derived azimuthally averaged RGB metallicities spanning 70 projected kpc along the GSS by modeling PAndAS CMDs as a combination of weighted isochrones and an MW foreground contamination model (Martin et al 2013). C18 obtained CMD-based metallicities for individual RGB candidates in pencil-beam Hubble Space Telescope/Advanced Camera for Surveys fields from Project AMIGA (Lehner et al 2020) and Brown et al (2006) targeting the GSS at 21, 52, and 80 projected kpc. Neither C16 nor C18 correct for contamination of the GSS by M31ʼs kinematically hot stellar halo, although they show that 1) fields probing the GSS in M31-centric coordinates.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…In addition, the most recent star formation in the GSS occured ∼4 Gyr ago, where the GSS has a typical stellar age of ∼8 Gyr (Brown et al 2006). Thus, a lower-mass progenitor would have produced lower 〈[α/Fe]〉 than is observed in the GSS: the progenitor's star formation would have quenched via interaction with M31ʼs ionized circumgalactic medium (Lehner et al 2020) only within the last few gigayears, providing sufficient time for Type Ia supernovae to deplete [α/Fe] with respect to [Fe/H]. The extended star formation history of the GSS similarly constrains the scenario of a high-mass progenitor (M å ∼ 10 10 M e ), although the interaction between M31 and the progenitor can begin as early as 5-10 Gyr ago in this case (D'Souza & Bell 2018;Hammer et al 2018).…”
Section: Implications For the Gss Progenitormentioning
confidence: 99%
“…XMM, ROSAT, and Chandra were used to study its X-ray emission (Stiele et al 2010). Ultraviolet (UV) measurements were used to study interstellar extinction (Clayton et al 2015) as well as the circumgalactic medium, finding a very extended ionized medium which may overlap with a similar one originating from our Milky Way (Lehner et al 2020). Optical and near-infrared (NIR) observations were used to investigate the stellar composition (Sick et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have begun to concentrate on absorption-line systems associated with more than one galaxy (Burchett et al 2016;Bielby et al 2017;Péroux et al 2017Péroux et al , 2019Pointon et al 2017;Pointon et al 2020;Nielsen et al 2018;Rahmani et al 2018a;Chen et al 2019;Hamanowicz et al 2020;Lehner et al 2020). It has been found that there is no strong anti-correlation between the equivalent width of Mg absorption and impact parameter for galaxy groups (Chen et al 2010b;Nielsen et al 2018), which differs from the strong anti-correlation found for isolated galaxies (e.g.…”
Section: Introductionmentioning
confidence: 93%